PRINSIP MORAL TERTINGGI: Konstruksi Nalar Maslahat Al-Buti dalam Wacana Ijtihad Kontemporer - M. Ilham Ilham (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2020)
This article aims to construct al-Buti> maslahat in contemporary ijtihad discourse as a grand narrative and the highest moral principle. The Methodology of this article is a library research which adopts descriptive analytical reading from various literatures with historical approaches include socio-cultural religious and philosophical approaches which include Islamic legal theories and Islamic legal philosophy. The dialectic of the text and benefit is a continuation of the classic debate between reason and revelation. The debate around the pattern of relations between the two colors the Muslim thought has passed to this day and has never been linear. Indeed form the highest moral principles of Islamic teachings, maslahah occupies an important position in the processes of ijtihad, especially in the latest development of socio-religious issues. Benefit considerations are impossible to deny because their existence as the ultimate goal of the Sabbath has a strong theological justification. Maslahah is the ultimate meaning of Islamic teachings that should be considered in understanding religious texts. Artikel ini bertujuan untuk mengungkap konstruksi nalar maslahat al-Buti> dalam wacana ijtihad kontemporer sebagai narasi agung dan prinsip moral tertinggi. Secara metodologis, artikel ini merupakan riset kepustakaan (library research) yang mengadopsi metode deskriptif analatis melalui pembacaan terhadap berbagai literatur dengan pendekatan pendekatan historis yang mencakup socio-cultural religious dan pendekatan filosofis yang meliputi teori hukum Islam (Islamic legal theories) dan filsafat hukum Islam (Islamic legal philosophy). Dialektika teks dan kemaslahatan merupakan kelanjutan perdebatan klasik antara nalar dan wahyu. Perdebatan seputar pola relasi antara keduanya mewarnai perjalanan pemikiran umat Islam sampai hari ini dan tidak pernah berjalan linier. Sejatinya, sebagai prinsip moral tertinggi ajaran Islam, kemaslahatan menempati posisi penting dalam proses-proses ijtihad, terlebih dalam perkembangan mutakhir isu sosial keagamaan. Pertimbangan kemaslahatan tidak mungkin dinafikan karena eksistensinya sebagai sebagai tujuan puncak pensyariatan memiliki justifikasi teologis yang kuat. Kemaslahatan merupakan makna puncak ajaran Islam yang semestinya dipertimbangkan dalam memahami teks-teks agama.